Depression and the apathy symptom are associated with poorer cognitive functioning in very old men: Developing topics. (7th December 2020) - Guerrero‐Berroa, Elizabeth; Schmeidler, James; Phillips, Ruby; Muallem, Julia; Suleiman, Halima; West, Rebecca; Sano, Mary; Reisberg, Barry; Silverman, Jeremy M
Abstract: Background: Older adults (65+) are among the fastest growing segments of the population, projected to double by 2050. Oldest‐old (85+) manifest the greatest relative increase in population and have the greatest risk of developing Alzheimer's Disease (AD). Depression is a chronic, debilitating condition in older adults. Depressive symptoms, particularly apathy—and poor concentration—have been associated with poor cognitive functioning and dementia. However, some associations depend upon gender, age of depression onset, and preexisting cognitive impairment; other studies find no association. Associations have been primarily in relatively young samples, and apathy has infrequently been studied in the very old. We investigated the cross‐sectional associations of depressive symptoms and apathy with cognitive functioning in cognitively normal very old men. Methods: Participants consisted of 74 cognitively intact male veterans (age = 86 ±5.1 [mean ± SD ], range = 76‐98; 81.1 % White, 18.9% Black; 15‐item Geriatric Depression Scale [GDS] = 2.6 ±2.7, range = 0‐12; 13.5% depressed [GDS ≥ 6]) enrolled in the Cardiovascular Risk Factors and Successful Cognitive Aging in Very Old Male Veterans study. The predictors were the GDS‐15 and the apathy item "Have you dropped many of your activities and interests?" Cognitive outcomes, from factor analysis of 11 neuropsychological test scores, were three Varimax factor cognitive domains (Episodic Memory, Attention, Executive Function), and the first principal component (global cognition). Linear regression analyses adjusted for age and education. Results: Depressive symptoms were significantly associated with poorer global cognition (r = ‐.274, p = .020). Apathy was significantly associated with poorer Attention (r = ‐.403, p < .001) and global cognition (r = ‐.377, p = .001). Apathy remained significant after controlling for the sum of other depressive symptoms. Conclusion: These results extend others' findings by showing that depressive symptoms, and specifically apathy, are associated with poorer cognitive functioning in very old men. This study highlights the relevance of examining depressive symptoms as predictors of cognitive functioning. The small effect sizes (r ≤ .097) for memory, the hallmark cognitive symptom of AD, suggest possible non‐AD biological involvement. Future studies with larger and more demographically and ethnically diverse samples are warranted.